Derivation and validation of a clinical prediction rule for thrombolysis-associated major bleeding in patients with acute pulmonary embolism: the BACS score. Issue 6 (3rd December 2020) - Jara-Palomares, Luis; Jiménez, David; Bikdeli, Behnood; Muriel, Alfonso; Rali, Parth; Yamashita, Yugo; Morimoto, Takeshi; Kimura, Takeshi; Le Mao, Raphael; Riera-Mestre, Antoni; Maestre, Ana; Moustafa, Fares; et al.
Background: Improved prediction of the risk of major bleeding in patients with acute pulmonary embolism (PE) receiving systemic thrombolysis is crucial to guide the choice of therapy. Methods: The study included consecutive patients with acute PE who received systemic thrombolysis in the RIETE registry. We used multivariable logistic regression analysis to create a risk score to predict 30-day major bleeding episodes. We externally validated the risk score in patients from the COMMAND VTE registry. In addition, we compared the newly created risk score against the Kuijer and RIETE scores. Results: Multivariable logistic regression identified four predictors for major bleeding: recent major bleeding (3 points), age >75 years (1 point), active cancer (1 point) and syncope (1 point) (BACS). Among 1172 patients receiving thrombolytic therapy in RIETE, 446 (38%) were classified as having low risk (none of the variables present, 0 points) of major bleeding according to the BACS score, and the overall 30-day major bleeding rate of this group was 2.9% (95% CI 1.6–4.9%), compared with 44% (95% CI 14–79%) in the high-risk group (>3 points). In the validation cohort, 51% (149 out of 290) of patients were classified as having low risk, and the overall 30-day major bleeding rate of this group was 1.3%. In RIETE, the 30-day major bleeding event rates in the Kuijer and RIETE low-risk strata were 5.3% and 4.4%, respectively. Conclusions: The BACS score is an easily applicable aid for prediction of the risk of major bleeding in the population of PE patients who receive systemic thrombolysis. The BACS score, based on easily available patient characteristics, could support physicians in their assessment of the risk of bleeding with systemic thrombolysis for acute pulmonary embolism https://bit.ly/3eVd0SH